2009
DOI: 10.1021/ic900276g
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Activities of Nickel(II) and Zinc(II) Complexes of Asymmetric [NN′O] Ligands as 26S Proteasome Inhibitors

Abstract: In this study, we compare the proteasome inhibition capabilities of two anticancer candidates, [Ni(LIA)2] (1) and [Zn(LIA)2] (2), where LIA- is the deprotonated form of the ligand 2,4-diiodo-6-(((2-pyridinylmethyl)amino)methyl)phenol. Species 1 contains nickel(II), a considerably inert ion that favors covalency, whereas 2 contains zinc(II), a labile transition metal ion that favors predominantly ionic bonds. We report on the synthesis and characterization of 1 and 2 using various spectroscopic, spectrometric, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 67 publications
(99 reference statements)
6
60
0
Order By: Relevance
“…These observations are consistent with the previous findings that nickel complex could not inhibit the 20S proteasome. 26,27 …”
Section: Resultsmentioning
confidence: 99%
“…These observations are consistent with the previous findings that nickel complex could not inhibit the 20S proteasome. 26,27 …”
Section: Resultsmentioning
confidence: 99%
“…A Zn(II) complex, along with a zinc salt, showed CT-like inhibitory effects when studied in vitro with purified 20S proteasome. Additionally, the zinc complex caused proteasome inhibition and apoptosis in C4-2B cancer cells, and also showed specificity towards cancer cells over normal MCF-10A breast cells [124]. Gallium(III)-containing compounds are also apoptosis inducers and can inhibit CT-like activity in prostate cancer cells; in one study, they demonstrated a 70% reduction in tumor growth [125].…”
Section: Natural Compounds and Repurposed Drugs With Proteasome-inhmentioning
confidence: 99%
“…The angles around the Zn II atom are from 81.53(7) to 120.79(5)°. The Zn-N [2.0469(2) and 2.1085(2) Å] bond lengths in the title structure are slightly shorter than those [2.149(6)-2.259(7) Å] in a similar complex [3]. The N-H···Cl hydrogen bonds link the complexes into one-dimensional chains which run along b.…”
mentioning
confidence: 84%
“…All other H-atoms were placed in calculated positions and treated as riding: C-H = 0.93 or 0.97 Å, with U iso (H) = 1.2 U eq (C). Discussion a-amino-pyridines metal complexes, in particular those of gallium(III), nickel(II) and zinc(II), have a great potential to be developed into novel anticancer drugs [1][2][3], and its cationic palladium complexes can catalyze the copolymerization of ethylene and norbornene [4]. The title complex was prepared by the reaction of ZnCl 2 with the potentially bidentate ligand N-(pyridin-2-ylmethyl)aniline.…”
Section: Methodsmentioning
confidence: 99%